Spatial analysis of gender-based high risks of school dropout: A comparative study of urban and rural areas in Sarawak, Malaysia - Danggat, Chabo; Tarmiji, Masron; Norita, Jubit; Azizul, Ahmad (UKM Press, 2026)
This study examines gender-based school dropout patterns in Sarawak, Malaysia through spatial analysis, comparing urban and rural regions. Using Getis-Ord Gi* hotspot analysis, statistically significant clusters of high dropout risk for boys and girls are identified. The results reveal distinct spatial disparities: female dropout hotspots are concentrated in specific rural districts, whereas male high-risk clusters emerge primarily in urban neighborhoods. These gender-specific geographic patterns suggest differing socio-economic and cultural drivers of dropout. These findings have important implications for educational policy, highlighting the need for targeted interventions that account for both gender and locality. By mapping dropout risk, the study provides new evidence to inform policies and resource allocation aimed at reducing gender disparities in school retention. The methodology can be applied in other contexts, offering a tool for international education planners to address local dropout challenges.